Strong spin-orbit interaction induced by transition metal oxides at the surface of hydrogen-terminated diamond. (30th August 2020) - Xing, Kaijian; Creedon, Daniel L.; Yianni, Steve A.; Akhgar, Golrokh; Zhang, Lei; Ley, Lothar; McCallum, Jeffrey C.; Qi, Dong-Chen; Pakes, Christopher I.
Abstract: Hydrogen-terminated diamond possesses an intriguing p -type surface conductivity which is induced via thermodynamically driven electron transfer from the diamond surface into surface acceptors such as atmospheric adsorbates, a process called surface transfer doping. High electron affinity transition metal oxides (TMOs) including MoO3 and V2 O5 have been shown to be highly effective solid-state surface acceptors for diamond, giving rise to a sub-surface two-dimensional (2D) hole layer with metallic conduction. In this work, low temperature magnetotransport is used as a tool to show the presence of a Rashba-type spin-orbit interaction with a high spin-orbit coupling of 19.9 meV for MoO3 doping and 22.9 meV for V2 O5 doping, respectively, through the observation of a transition in the phase-coherent backscattering transport from weak localization to weak antilocalization at low temperature. Surface transfer doping of diamond with TMOs provides a 2D hole system with spin-orbit coupling that is over two times larger than that reported for diamond surfaces with atmospheric acceptors, opening up possibilities to study and engineer spin transport in a carbon material system. Graphical abstract: Image 1